The Financial Crisis of the Eurozone - Marttinen , Tuomas (International Journal of Multidisciplinary in Management and Tourism, 2020)
This study is made about the financial crisis of the eurozone. The purpose of this study is to find answers about the causes of the ongoing financial and economical crisis of the eurozone. It is also very important to find the solution to the problem that how they are going to solve these financial and economical problems in the eurozone. This study is important, because the financial and economical problems are influencing to the economies and countries in all over the world. This study is going to give answers to the reasons why there is financial and economical problems in the eurozone and what kind of solutions they have to do to be able to solve this difficult siutuation in Europe. After analyzing the data, the study found that there were many different reasons why the financial crisis started in the eurozone. There was a housing bubble in the United States in 2006, and from there the situation spreaded in all over the world. One of he America´s largest investment banks, Lehman Brothers, collapsed and that scared the banks and investors globally. The reason why there was economical and financial problems in the United States is that there was slowdown in their economy and because of that the homeowners defaulted on their mortgages. There was banks around the world which had investments that were linked to those American mortgages, and because of the difficult economic situation of the United States, they started to lose money. The financial crisis has been affecting to the member countries of the eurozone since 2009. The reason why the crisis began in Europe was that there was a group of central and eastern European banks which were asking for bailout. The study refers that the financial and economical crisis is a combination of government debt crisis, banking crisis, and growth and competetiveness crisis. There is many structural weaknesses in the European Union and they need to improve the polcycoorination between the member countries. Because the economic governance of the European Union was so weak, countries like Greece, Spain, Ireland, Portugal, and Cyprus had very serious financial and economical problems. The study concludes that they have to improve the policy coordination, and economic and financial surveillance in the eurozone, if they want to prevent this kind of economical and financial problems from rising again.